Kolaborasi Metode Diskusi Kelompok Dengan Problem Solving Learning Untuk Meningkatkan Keterampilan Pemecahan Masalah Siswa Pada Materi Aqidah Akhlak - Rubi Babullah; Siti Qomariyah; Neneng Neneng; Ujang Natadireja; Siti Nurafifah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to determine the implications of collaborating group discussion methods with Problem Solving Learning in improving students' problem solving skills at SDN Pelita Jaya. This research uses qualitative research methods with a mini research approach to gain in-depth insight into interactions between students in structured learning. For three weeks, research was conducted at SDN Pelita Jaya involving sixth grade students. The group discussion method is used to facilitate student interaction in discussing Islamic ethical and moral values. Students are also given ethical situations or problems that require them to find solutions based on Islamic moral principles through the Problem Solving Learning approach. Qualitative data was collected through participant observation, interviews with students, and document analysis. The results of the analysis show a significant increase in students' ability to identify, analyze and overcome problems with a structured and directed approach. Apart from that, this collaborative learning method also strengthens student involvement in the learning process. This research provides in-depth insight into the positive potential of collaborative group discussion methods with Problem Solving Learning in improving students' problem solving skills. The results of these findings can provide a valuable contribution to the development of more effective learning strategies, especially in Islamic Religious Education subjects.